CONTEMPORARY PATHOGENETIC MECHANISM OF SYSTEMIC SCLERODERMA (World Bulletin of Public Health, 2023)
Systemic scleroderma is a chronic and often progressive autoimmune inflammation of connective tissue, characterized by fibrosis of the skin and internal organs, common vascular damage with unexplained etiology and heterogeneous clinical manifestations. Systemic scleroderma is a disorder of collagen synthesis and accumulation in the skin (scleroderma) and other internal organs, especially in the connective tissue of the lungs, gastrointestinal tract (gastrointestinal tract), heart and kidneys. Over time, patients show signs of progressive structural and functional impairment of blood vessels and internal organs due to fibrosis. This review article presents current data on the pathogenetic mechanisms of systemic scleroderma
Keywords: Systemic scleroderma; antinuclear antibodies; T-cells